Implementasi Integrated Marketing Communication (IMC) Pada Sofie Localfood - Fitriah Hartanti; Ira Nuriya Santi; Zakiyah Zahara; Wiri Wirastuti (Journal Economic Excellence Ibnu Sina, 2024)
The more businesses that are established, especially those operating in the same field, this can create competition which can be a challenge for the company. In this case, the business is not just about buying and selling, but must prioritize the opportunity to reach consumers in a good way. One of the main keys is effective communication. The method that will be used in this research is qualitative descriptive. Research with a qualitative descriptive design aims to understand the phenomena experienced by research subjects which include behavior, motivation. According to the company, Sofie implements marketing communications such as advertising, sales promotions, personal sales and public relations. The advertising carried out aims to introduce products to the public, according to information from CV Sofie Localfood, which predominantly uses below the line media such as pamphlets, pamphlets which are created and distributed online via social media accounts such as Instagram, Facebook, whatsappSofie localfood in retaining its customers has implemented Integrated Marketing Communication (IMC) or Integrated Marketing Communication in the form of advertising, sales promotions, direct marketing, personal selling and public relations. In Integrated Marketing Communication, the most important thing is to unite various marketing communication elements that are usually carried out separately